Randomized pilot trial of the “Mom Power” trauma- and attachment-informed multi-family group intervention in treating and preventing postpartum symptoms of depression among a health disparity sample - Jester, Jennifer M.; Riggs, Jessica L.; Menke, Rena A.; Alfafara, Emily; Issa, Meriam; Muzik, Maria; Rosenblum, Katherine L. (Frontiers in Psychiatry, 2023)
Introduction Perinatal depression, a common complication related to childbearing, impacts mothers, children, and families. Efficacious interventions reduce perinatal depression symptoms; effort is needed to prevent the onset of perinatal depression. To determine feasibility and preliminary efficacy in reducing perinatal depression, we conducted a community-based, randomized parallel open pilot trial of Mom Power, a group-based intervention to improve mental health and parenting in mothers with young children.Methods Mom Power consists of 10 group sessions, focused on parenting, child development and self-care and three individual sessions, to build rapport and provide personalized referrals. Control group participants received psychoeducational mailings. Computer-based urn randomization assigned mothers with experiences of interpersonal violence, depression, or other traumatic experiences to Mom Power (68) or control (54).Results At 3-months post-treatment, the 31 retained women assigned to Mom Power were half as likely to meet criteria for probable depression (26%) as the 22 women retained in the control group (55%), with treatment predicting lower incidence of probable depression (OR = .13, p = .015). Moreover, among the 23 women who did not meet criteria for depression diagnosis at baseline, no women in the treatment group developed depression (n = 0, 0%) compared to control group women (n = 3, 30%). Logistic regression controlling for selective attrition confirmed the treatment effect on preventing new onset of depression (OR = .029, p = .012) Conclusion These findings support the use of Mom Power for both treatment and prevention of perinatal depression.Clinical trial identifier NCT01554215 https://classic.clinicaltrials.gov/ct2/show/NCT01554215.